Measuring Speaking Gains from Hello Talk Use in Eleventh Grade: Quasi‑Experimental Evidence - Ardhita Chairunnisa; Husnaini Husnaini; Darmawan Budiyanto; Heru Setiawan (Indonesian Language Education and Applied Linguistics Reviews, 2026)
The objective of this study was to evaluate the effectiveness of the HelloTalk application in improving the speaking proficiency of eleventh-grade students at SMA Negeri 4 Palembang. A quantitative quasi-experimental design was employed, involving 120 students selected through purposive sampling and divided into experimental and control groups. The study used a pretest-posttest design to measure fluency, accuracy, grammar, mechanics, and pronunciation during an eight-week intervention with HelloTalk. The instrument’s content validity was confirmed using expert judgment and Aiken’s V formula, while data analysis was conducted through SPSS 24. The Kolmogorov-Smirnov test confirmed normal data distribution (p > 0.05). An independent sample t-test revealed a statistically significant difference in speaking performance between students taught using HelloTalk and those without, with a p-value of 0.000 (< 0.05). The findings indicate that HelloTalk substantially enhanced students’ speaking proficiency, particularly in fluency and self-expression, after consistent use over eight weeks. These results highlight the application’s positive impact on EFL learning and align with recent research promoting mobile and AI-assisted tools for language development. Thus, HelloTalk proves to be an effective platform to support formal classroom instruction in improving students’ English-speaking skills.